The Impact of Highest Rally Training on Improving Drive Shot Ability in Squash Games - Irvan; Syafruddin, Muhammad Akbar; Sufitriyono (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The goal of this research is to ascertain how high-level rally training affects students' efforts to improve their forehand drive and hitting ability in squash at Makassar State University's Faculty of Sports Science. The sampling technique we used was a random selection of 33 male students. We employed the t-test to analyze the data. The data analysis results indicate that the mean difference between the average pre-test and post-test scores is -13.879, and the sig. 2-tailed is 0.000 or <0.05. Therefore, the highest level of rally training impacts efforts to enhance students' squash forehand driveability, as indicated by the mean difference between the pre-test and post-test scores.